User‐level parallel file system: Case studies and performance optimizations. (28th February 2022) - Zou, Yanliang; Chen, Chen; Deng, Tongliang; Zhang, Jian; Zhu, Xiaomin; Chen, Si; Yin, Shu
Abstract: User‐level file systems are usually adopted to bridge the gap between efficacy and efficiency of file system developments for new applications' I/O demands. And the widely known user‐space file system framework, FUSE, is commonly utilized to deployed user‐level file systems. This article first uses a popular stack‐able file system as a case study to exam how FUSE affects I/O performance. Based on the testing and analytical results, this article then presents SHC, an implementation method to implement a user‐level file system without FUSE intervention. Experimental results indicate that SHC improves write bandwidth by up to 5.6x compared with that of FUSE and present leading superiority on read cases.